Perbandingan Nilai Index Exposure pada Radiografi Thorax dengan Perubahan Kombinasi Nilai mA dan s Berbeda pada Nilai mAs yang Sama - Angga Yosainto Bequet; Susi Tri Isnoviasih (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: In CR, there is an indicator called Exposure Index (EI) which displays how much exposure is used for a particular examination. The Exposure Index depends on the exposure factor, the total area of the detector exposed to radiation, and the object being exposed (Bontrager Lampignano, 2014). One of the exposure factors that is often regulated by the radiographer is mAs. Milliampere seconds (mAs) determine the number of X-rays produced. The purpose of this study was to determine the differences in the Exposure Index Values on Chest Radiography with Changes in the Combination of Different mA and s Values at the Same mAs Value.Methods: This research is a type of quantitative research with a pre-experimental design. The object of this research is the thorax phantom. Data were collected by exposing thorax the chest phantom, then recording the resulting Exposure Index value. mA and s value variations that are set are 25mA x 320 ms, 160mA x 50 ms and 400mA x 20ms. Data analysis was carried out using statistical tests.Results: From the statistical test results it is known that there is no significant difference in the Exposure Index Value on Thorax Radiography between the 25mA x 320 ms combination group, the 160mA x 50 ms combination and the 400mA x 20ms combination with a p-value 0.05 (p-value = 0.151) . The reason for the absence of a difference in the Exposure Index value is the variation in the combination of different mA and s values for the same mAs because with the same mAs, the quantity / intensity value of the X-ray radiation produced is also the same or there is no increase or decrease. With the same x-ray radiation intensity, the radiation received by the Imaging Plate is also the same so that the value of the Exposure index is also the same.Conclusions: There is no significant difference in the Exposure Index Value on Chest Radiography with Changes in the Combination of Different mA and s Values at the Same mAs Value